Strategi Pengembangan Wisata Berbasis Kearifan Lokal pada Desa Wisata Pagerharjo Kecamatan Samigaluh Kabupaten Kulon Progo Yogyakarta - Sukmadi Sukmadi; Faisal Kasim; Violetta Simatupang; Andar Danova L. Goeltom; Indra Saftara (Politeknik Pariwisata NHI Bandung, 2020)
This study aims to identify and analyze tourism development strategies based on local wisdom in the tourism village of Pagerharjo, Samigaluh District, Kulon Progo Regency, Yogyakarta. The method used in this study is a descriptive qualitative method with a case study approach. Sources of data in this study are primary funds and secondary data. Primary data were obtained through interviews and field observations. While the data analysis technique used is data analysis using the interactive model of analysis developed by Miles and Hubermann. The results showed that (1) The potential of local wisdom that can be packaged and developed as a tourist attraction in the Tourism Village of Pagerharjo is mutual cooperation, nguri-uri oral traditions, suronan, reog cultural traditions, jathilan, incling, angguk, campur sari, kethoprak, puppeteer and what is characteristic is the lengger tapeng dance, while from a culinary perspective there is taro leaf butyl, geblek, which can still be witnessed and enjoyed today; (2) Aspects that must be considered in planning tourism development in the Tourism Village of Pagerharjo are (a) the low level of community human resources in the development of tourism villages; (b) Poor tourism village institutional governance; (c) Low optimization of local products (food, crafts, arts); (d) The absence of participatory planning in the development of tourism villages; (3) The supporting factors for the development of tourism based on local wisdom in the Tourism Village of Pagerharjo include the community culture that has been attached to the attitude of courtesy and hospitality to anyone who comes. While the inhibiting factors include the absence of a blueprint for mapping the tourism potential in Pagerharjo village, community empowerment from upstream to downstream which has not been running and communication factors between the community, village government and all elements involved in it need to be improved so that harmonious communication is formed.